2016
DOI: 10.1186/s13287-016-0394-0
|View full text |Cite
|
Sign up to set email alerts
|

Secreted trophic factors of mesenchymal stem cells support neurovascular and musculoskeletal therapies

Abstract: Adult mesenchymal stem cells (MSCs) represent a subject of intense experimental and biomedical interest. Recently, trophic activities of MSCs have become the topic of a number of revealing studies that span both basic and clinical fields. In this review, we focus on recent investigations that have elucidated trophic mechanisms and shed light on MSC clinical efficacy relevant to musculoskeletal applications. Innate differences due to MSC sourcing may play a role in the clinical utility of isolated MSCs. Pain ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
208
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(210 citation statements)
references
References 175 publications
(179 reference statements)
1
208
0
1
Order By: Relevance
“…A wide range of evidence indicates that paracrine effects of MSC are a central mechanism of cell therapy promoting tissue regeneration [29, 30]. In line with this view, we have previously shown that CM from ADMSC exhibits anti-inflammatory properties in OA chondrocytes [20].…”
Section: Discussionsupporting
confidence: 56%
“…A wide range of evidence indicates that paracrine effects of MSC are a central mechanism of cell therapy promoting tissue regeneration [29, 30]. In line with this view, we have previously shown that CM from ADMSC exhibits anti-inflammatory properties in OA chondrocytes [20].…”
Section: Discussionsupporting
confidence: 56%
“…Because the delivery of regenerative trophic factors to the site of injury is now being considered the primary mechanism of MSC‐mediated tissue repair (Fu et al, ; Hofer & Tuan, ), the levels of VEGF, SCF, and IL‐6 were quantified in cell culture supernatants on Days 1, 5, 8, and 12 (Figure a–c). VEGF is an angiogenic and pro‐regenerative growth factor (Arsic et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning factors released by MSCs that could be involved in the acquisition of chemoresistance by tumor cells, several authors have identified CCL5, IL-6 and the C-X-C motif chemokine ligand 8 (CXCL8 or IL-8) [16][17][18]. This last cytokine has been implicated in a number of inflammatory diseases involving the chemo-attraction and activation of neutrophils.…”
Section: Introductionmentioning
confidence: 99%